Identifikasi Sebaran Bijih Besi Menggunakan Metode Geomagnet di Desa Pringgabaya Utara, Kabupaten Lombok Timur - Ulfa Eka Safitri; Teguh Ardianto; Lily Maysari Anggraini (Universitas Hamzanwadi, 2020)
Research has been conducted which aims to determine the distribution of rocks containing iron ore using the geomagnetic method in the North Pringgabaya Village, East Lombok Regency, NTB. Retrieval of magnetic data was carried out with the Proton Precision Magnetometer (PPM) GEM-19T v7.0 in an area of 4 km2 with a measurement point spacing of 100 m and spacing between trajectories of 200 m. From the measurement data, daily and IGRF corrections were performed to obtain total magnetic anomaly contours. Upward continuation is carried out to separate regional and residual magnetic anomalies at an altitude of 200 m. The results showed that there were indications of iron ore in the area with magnetic anomaly data ranging from -147.6 nT to 594.8 nT. The results showed that the rocks identified as iron ore were sand which were mostly found in the eastern and western parts of the study area with a susceptibility value of 0.01634885 SI up to 0.02674884 SI at a depth of 153 m to 449 m.DOI: 10.29408/kpj.v4i1.2086.